Association between biophilic home office setting and academicians’ perceived performance by using SMARTPLS / Mohamad Haizam Mohamed Saraf ... [et al.] - Mohamed Saraf, Mohamad Haizam; Ahmad, Nursaadatun Nisak; Abdul Tharim, Asniza Hamimi; Che Ahmad, Asmalia; Raffikhul, Nur Qamarina (2021)
Prior research has documented that the natural elements or biophilia and the office setting have positive effects towards personnel performance and well-being. Yet, less emphasis has been given to the personnel who are working at home due to the sudden shift from working at office to working from home because of Covid-19 pandemic. In view of that, this study aims to examine the association between biophilic home office setting and academicians’ perceived performance. 260 questionnaire responses from academicians who work from home due to Covid-19 were analyzed by using Statistical Package for the Social Sciences (SPSS) version 25.0 and SMARTPLS; a partial least squares-structural equation (PLS-SEM) modeling software for hypothesis testing. The results of the hypothesis testing show that biophilic elements in a home office setting showed perceived enhancement of the academician’s performance. Subsequently, the findings will contribute in the development of a comprehensive biophilic design elements model for home office setting.